Selection and characterization of specific nanobody against neuropilin-1 for inhibition of angiogenesis. (December 2020) - Naderi, Shamsi; Roshan, Reyhaneh; Ghaderi, Hajarsadat; Behdani, Mahdi; Mahmoudi, Sara; Habibi-Anbouhi, Mahdi; Shokrgozar, Mohammad Ali; Kazemi-Lomedasht, Fatemeh
Highlights: High affinity Nanobodies against NRP-1 were isolated from immune libraries. Selected Nanobodies inhibited in vitro and in vivo angiogenesis. Results indicated for potential of nanobodies as novel cancer therapeutics. Abstract: Neuropilin-1 (NRP-1), non-tyrosine kinase receptor, was initially identified as axonal protein and later recognized as co-receptor for vascular endothelial growth factor (VEGF). Neuropilins (NRPs) are involved in vascular development and tumor angiogenesis. Over the last years, many studies have been accomplished to inhibit angiogenesis. In this study, the nanobody library was panned against immobilized NRP-1 antigen. High affinity and specificity nanobodies were selected through monoclonal ELISA. The selected nanobodies inhibited proliferation and tube formation of HUVEC and MCF-7 cells in vitro and ex vivo . The results highlight potential of anti-NRP1 nanobodies in inhibition of angiogenesis both in vitro and ex vivo and promises development of novel therapeutics against pathologic angiogenesis.